A home close to opportunities in South Africa: top down vision or bottom up demand? - Landman, Karina (Department of Urban and Regional Planning, University of the Free State, 2010)
South African cities have changed tremendously over the past 50 years. Alongside growing urbanisation, people have moved further apart or closer to each other, influenced by the reigning ideologies and policies of the past and present. Cities were and are shaped by the leading corporations, institutions and to some extent by the planners who aim to implement their visions. Many of the contemporary international planning and urban design movements promote closer proximity of new housing developments to a larger variety of socio-economic opportunities. In response, international planning and development policies from many countries advocate the development of medium-density mixed housing developments to achieve increased densification and socio-economic integration and ultimately more sustainable cities. The new housing plan, Breaking New Ground (2004), also promotes this. Yet, how many people pause to consider the opinions of those for whom these developments are planned and designed? This discussion reconsiders the issue of housing location and, in particular, the importance of greater proximity of housing projects to a range of socio-economic opportunities from a resident’s point of view.

Suid-Afrikaanse stede het geweldig baie verander in die laaste 50 jaar. Tesame met verstedeliking en beïnvloed deur verskeie ideologië en beleidsdokumente, het mense ruim-telik verder of nader aanmekaar beweeg. Stede was en word gevorm deur groot korporasies, institusies en tot ‘n mate deur beplanners wat probeer om hulle visies te implementeer. Vele kontemporêre internasionale beplannings- en stedelike ontwerpbewegings verkies dat nuwe behuisingsprojekte naby aan ‘n verskeidenheid van sosiale en ekonomiese geleenthede geleë behoort te wees. In reaksie hierop word die ontwikkeling van mediumdigtheids-, gemengde behuising voorgehou om hoërdigtheidsontwikkeling en sosiale en ekonomiese integrasie, asook meer volhoubare ontwikkeling te bewerkstellig. Die nuwe behuisingsplan in Suid-Afrika, Breaking New Ground (2004), moedig ’n ooreenstemmige benadering aan. Tog, hoeveel mense stop vir ‘n oomblik om die opinies van die mense wat hier moet bly te bepaal? Hierdie bespreking heroorweeg die ligging van behuising en meer spesifiek die belangrikheid van nabygeleë sosiale en ekonomiese geleenthede aan nuwe behuisingsprojekte volgens die inwoners.

Metsemeholo ya Afrika Borwa e fetohile haholo dilemong tse mashome a mahlano (50) tse fetileng. Ha mmoho le kgolo dibakeng tsa metse ya ditoropo, batho ba dula hole le ba bang kapa ba dula haufi le ba bang, ba tshwaetswa le ho hemelwa ke mehopolo ya ho busa le ya mano a nakong e fetileng le mehla ya kajeno. Metsemeholo e ne e botjwa ke dikoporeishene tse tummeng, dibaka tsa tshebetso tse itseng mme le ho feta moo le baradi bao sepheo sa bona e leng phethahatsa ditjhebelopele tsa bona. Bongata ba mekgatlo ya nakong e fetile ya meralo ya matjhaba le ya meralo ya metse ya ditoropo e tlisa ntlafatso haufiufi le dintshetsopele tsa matlo tse ntjha ho ya ho maemo a fapafapaneng a maholo a menyetla ya tsa phedisano le moruo. Karabong ya tsena, ba moralo wa matjhaba esitana le mano a ntshetsopele ho tswa dinaheng tse tse ding ngata di bontsha nthetsopele ya dintshetsopele tsa bongata bo bohareng bo kopakopaneng ho fihlella bongata ba matlo bo eketsehileng le kopano ya phedisano le moruo mme qetellong ho be le metsemoholo e ka kgona ho itsamaisa. Mora o motjha wa matlo, e leng Ho Kenya Mohoma Temeng (Breaking New Ground) (2004), le wona o ntlafatsa sena.Empa, kgele! Ke batho ba bakae kgefutsang mme ba tadima maikutlo a batho bao, bao ba reretsweng dintshetsopele tsena le ho di rallwa? Puisano ena e boela e tadima hape taba ya tulo ya moo matlo a hahuwang teng, haholoholo ya bohlokwa ba bohaufi bo boholo ba mesebetsi (diprojeke) ya matlo ho fihlella menyetla ya phedisano le moruo ho tswa tjhadimong ya moahi.
Keywords: Urbanisation; Policies; Mixed housing; Housing location